1977
DOI: 10.1111/j.1939-0025.1977.tb01255.x
|View full text |Cite
|
Sign up to set email alerts
|

The nature of the symbiotic bond between mother and schizophrenic.

Abstract: Based on objectively scored TAT stories and interviews measuring five aspects of symbiotic relationships, a group of schizophrenics and their mothers showed more evidence of being enmeshed in such a relationship than did both non‐schizophrenic mental patients and a group of normals and their mothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
1

Year Published

1979
1979
2005
2005

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
2
14
1
Order By: Relevance
“…This evidence supports the difference between functional overprotectiveness found in most parent-child relationships and a symbiotic relationship characterized by overdependency, disapproval of other relationships, separation difficulties, intrusiveness, and injunctions against achieving personal autonomy (Summers, 1978;Summers & Walsh, 1977). This evidence supports the difference between functional overprotectiveness found in most parent-child relationships and a symbiotic relationship characterized by overdependency, disapproval of other relationships, separation difficulties, intrusiveness, and injunctions against achieving personal autonomy (Summers, 1978;Summers & Walsh, 1977).…”
Section: Symbiosissupporting
confidence: 73%
“…This evidence supports the difference between functional overprotectiveness found in most parent-child relationships and a symbiotic relationship characterized by overdependency, disapproval of other relationships, separation difficulties, intrusiveness, and injunctions against achieving personal autonomy (Summers, 1978;Summers & Walsh, 1977). This evidence supports the difference between functional overprotectiveness found in most parent-child relationships and a symbiotic relationship characterized by overdependency, disapproval of other relationships, separation difficulties, intrusiveness, and injunctions against achieving personal autonomy (Summers, 1978;Summers & Walsh, 1977).…”
Section: Symbiosissupporting
confidence: 73%
“…Although evidence for genetic determinants exists (3), such factors cannot by themselves explain the appearance of schizophrenia. Previous studies have found evidence that the relationships between each parent and the schizophrenic young adult are markedly different from the relationships between other young adults (both mentally ill and normal) and their parents (10, 11). The mother‐schizophrenic relationship appears to be characterized by a symbiotic bond, whereas the father evinces a failure to accommodate to his schizophrenic offspring.…”
mentioning
confidence: 95%
“…The current study attempted to determine the extent of symbiosis and confirmation in the relationship of the parents of the schizophrenic in an objective, verifiable manner. It thus seeks to complement previous reports that attempted this task for the mother‐ and father‐schizophrenic dyads (10, 11). By measuring the degree to which the characteristics previously found in the mother‐ and father‐ schizophrenic dyads obtain in the mother‐father relationship, the current study completes a systematic investigation of the degree of differentiation in the family system of the schizophrenic.…”
mentioning
confidence: 99%
See 2 more Smart Citations